Interlayer excitons in MoSe2/WSe2 heterostructures from first principles - Gillen, Roland; Maultzsch, Janina (Physical Review B, 2018)
Based on ab initio theoretical calculations of the optical spectra of vertical heterostructures of MoSe2 (or MoS2) and WSe2 sheets, we reveal two spin-orbit-split Rydberg series of excitonic states below the A excitons of MoSe2 and WSe2 with a significant binding energy on the order of 250 meV for the first excitons in the series. At the same time, we predict from accurate many-body G(0)W(0) calculations that crystallographically aligned MoSe2/WSe2 heterostructures exhibit an indirect fundamental band gap. Due to the type-II nature of the MoSe2/WSe2 heterostructure, the indirect transition and the exciton Rydberg series corresponding to a direct transition exhibit a distinct interlayer nature with spatial charge separation of the coupled electrons and holes. Our calculations confirm the recent experimental observation of a doublet nature of the long-lived states in photoluminescence spectra of MoX2/WY2 heterostructures, and we attribute these two contributions to momentum-direct interlayer excitons at the K point of the hexagonal Brillouin zone and to momentum-indirect excitons at the indirect fundamental band gap. Our calculations further suggest a noticeable effect of stacking order on the electronic band gaps and on the peak energies of the interlayer excitons and their oscillation strengths.
Keywords: excitons; TMDC; first-principles calculations; heterostructure